Allelopathic effect of trees grown in homesteads of Kerala on turmeric (Curcuma longa Linn.) - Sruthi Lakshmi P G (Department of agronomy, College of agriculture, 2015)
The experiment entitled “Allelopathic effect of trees grown in homesteads of Kerala on turmeric (Curcuma longa Lin.)” was undertaken at College of Agriculture, Padannakkad during the period from April 2014 to January 2015. The study involved two laboratory bioassays and two pot culture experiments. The main objective of the study was to investigate the allelopathic effect of certain multipurpose trees commonly planted in the homestead gardens of Kerala on sprouting, growth and yield of turmeric. The first experiment (Bioassay I), laid out in completely randomized design, comprised of thirteen treatments replicated thrice viz., T1 [leaf leachates of coconut (1:10)], T2 [Cashew (1:10)], T3 [Jack (1:10)], T4 [Mango (1:10)], T5 [Tamarind (1:10)], T6 [Teak (1:10)], T7 [Coconut (1:15)], T8 [Cashew (1:15)], T9 [Jack (1:15)], T10 [ Mango (1:15)], T11 [ Tamarind (1:15)], T12 [Teak (1:15)], and T13 (Ordinary tap water). The second experiment (Bioasay II) was also conducted in the same manner as the first bioassay but using tree leaf extracts instead of leaf leachates as the treatments. The third experiment (Pot culture I) was laid out in completely randomized design using the same thirteen treatments as in the first experiment and replicated thrice. The fourth experiment (Pot culture II), laid out in completely randomized design, comprised of seven treatments replicated thrice viz., T1 (Mulching with fresh leaf loppings of coconut), T2 (Cashew), T3 (Jack), T4 (Mango), T5 (Tamarind), T6 (Teak), T7 (News paper). These mulches were at the rates recommended in the Package of Practices Recommendations for crops by the Kerala Agricultural University. Turmeric variety ‘Sobha’ was raised for the experiment. In the first bioassay, it was observed that the leaf leachates of tamarind, teak, jack (at 1:10 and 1:15 concentration) and cashew and mango (at 1:10) severely inhibited sprouting. All the tree leaf leachates except cashew and mango (1:15) severely inhibited the shoot growth. All the leaf leachates except coconut and cashew at lower concentration remarkably inhibited the root growth. In the second bioassay, leaf extracts of all the trees except cashew and jack considerably reduced the sprouting of rhizomes. Higher concentration of mango caused most severe inhibition (73%) followed by teak (1:10). Shoot growth of turmeric seedlings was inhibited by the leaf extracts of all trees except coconut (1:10), cashew (1:15) and jack (1:15). The leaf extract of teak (1:10) suppressed shoot growth most severely followed by mango (1:10). Root growth was inhibited by the leaf extracts of all trees. In the first pot culture experiment, coconut leaf leachate at both concentrations resulted in greater plant height at 4 and 6 MAP. Leaf production was notably affected at 4 and 6 MAP when sprayed with teak leaf leachate at higher concentration. The teak leachate (1:10) reduced root spread remarkably. Root weight was appreciably less in plants treated with leaf leachate of teak (at both concentrations) and tamarind at higher concentration. Root volume was conspicuously less when subjected to higher concentration of tamarind leaf leachate. The coconut leaf leachates at both concentrations, jack and tamarind (1:10) and cashew (1:15) resulted in considerably higher yield. The leaf leachates of mango (1:10) and teak (1:10) reduced the yield.